ACE gene I/D polymorphism and severity of SARS-CoV-2 infection in hospitalized patients: a metanalysis - Romero-Ortuno, Roman (My University, 2021)
Background Hypertension and type 2 diabetes increase the risk of severe SARS-CoV-2 infection. On the other hand, homozygous ACE deletion polymorphism (DD) has been associated with these two diseases and risk of acute respiratory distress syndrome. Aim To conduct a metanalysis of the association between ACE gene I/D polymorphism (DD, II and DI) and severity of SARS-CoV-2 infection in hospitalized patients. Methods We searched PubMed, EMBASE and Google Scholar for studies published between January 2020 and April 2021. We included case-control studies evaluating the association between ACE I/D and severity of SARS-CoV-2 infection in hospitalized patients, were there was sufficient genotype or allele frequency data to calculate IRR (incidence rate ratio) and 95% confidence intervals (CIs). Results 5 studies were included (mean age 58.5 years and 61% men), combining to a total of 786 patients. Three studies were conducted in Caucasians. Overall, patients who had homozygous co-dominance genotype DD were at 47% higher risk of severe COVID-19 compared with II or ID (IRR: 1.47; 95% CI: 1.15-1.89; p=0.002). Conclusions The ACE DD genotype may confer a greater risk of severe COVID-19 in hospitalized patients. Further studies including more diverse ethnic groups are necessary to fully establish this association.
PUBLISHED
Keywords: ACE gene; I/D polymorphism; SARS-CoV-2; COVID-19; Meta-analysis; Ageing; Immunology, Inflammation & Infection; Age-related disability; Health; Third age/ageing